Anthropometric and physical indicators among Jordanian female soccer according to playing position - Ghazi El-kalana; Sofia Akroush; Salem Al-qarra; Osama Abdel Fattah; Mousa Ahmad (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Soccer requires specific indicators to help achieve athletic accomplishments, including anthropometric measurements linked to physiological capacities and significantly influencing fitness levels.